Movement Disorders Associated With Cerebral Artery Stenosis: A Nationwide Study - Park, Kye Won; Choi, Nari; Oh, Eungseok; Lyoo, Chul Hyoung; Baek, Min Seok; Kim, Han-Joon; Yoo, Dalla; Lee, Jee-Young; Choi, Ji-Hyun; Lee, Jae Hyeok; Koh, Seong-Beom; Sung, Young Hee; et al. (Frontiers in Neurology, 2022)
Background: Studies of secondary movement disorder (MD) caused by cerebrovascular diseases have primarily focused on post-stroke MD. However, MD can also result from cerebral artery stenosis (CAS) without clinical manifestations of stroke. In this study, we aimed to investigate the clinical characteristics of MD associated with CAS. Materials and Methods: A nationwide multicenter retrospective analysis was performed based on the data from patients with CAS-associated MDs from 16 MD specialized clinics in South Korea, available between January 1999 and September 2019. CAS was defined as the > 50% luminal stenosis of the major cerebral arteries. The association between MD and CAS was determined by MD specialists using pre-defined clinical criteria. The collected clinical information included baseline demographics, features of MD, characteristics of CAS, treatment, and MD outcomes. Statistical analyses were performed to identify factors associated with the MD outcomes. Results: The data from a total of 81 patients with CAS-associated MD were analyzed. The mean age of MD onset was 60.5 ± 19.7 years. Chorea was the most common MD (57%), followed by tremor/limb-shaking, myoclonus, and dystonia. Atherosclerosis was the most common etiology of CAS (78%), with the remaining cases attributed to moyamoya disease. Relative to patients with atherosclerosis, those with moyamoya disease developed MD at a younger age (p < 0.001) and had a more chronic mode of onset (p = 0.001) and less acute ischemic lesion (p = 0.021). Eight patients who underwent surgical treatment for CAS showed positive outcomes. Patients with acute MD onset had a better outcome than those with subacute-to-chronic MD onset (p = 0.008). Conclusions: This study highlights the spectrum of CAS-associated with MD across the country. A progressive, age-dependent functional neuronal modulation in the basal ganglia due to CAS may underlie this condition.